Design of flat pneumatic artificial muscles. (7th February 2017) - Wirekoh, Jackson; Park, Yong-Lae
Abstract: Pneumatic artificial muscles (PAMs) have gained wide use in the field of robotics due to their ability to generate linear forces and motions with a simple mechanism, while remaining lightweight and compact. However, PAMs are limited by their traditional cylindrical form factors, which must increase radially to improve contraction force generation. Additionally, this form factor results in overly complicated fabrication processes when embedded fibers and sensor elements are required to provide efficient actuation and control of the PAMs while minimizing the bulkiness of the overall robotic system. In order to overcome these limitations, a flat two-dimensional PAM capable of being fabricated using a simple layered manufacturing process was created. Furthermore, a theoretical model was developed using Von Karman's formulation for large deformations and the energy methods. Experimental characterizations of two different types of PAMs, a single-cell unit and a multi-cell unit, were performed to measure the maximum contraction lengths and forces at input pressures ranging from 0 to 150 kPa. Experimental data were then used to verify the fidelity of the theoretical model.